Inovasi Produk Bersama IRT pada Usaha Anyaman di Desa Gundik, Slahung, Ponorogo - Sedinadia Putri (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2021)
Wicker crafts basically have good potential. Because it has a high aesthetic value and appeal to consumers. However, the products produced in this business are still less innovative, namely only woven bags. So productivity in this business is still not going well. In addition, around the business there are still many housewives (IRT) who do not have activities during the day. The purpose of this community service is to develop woven craft products and provide assistance for IRT around the business through product innovation box hantaran. This is done as an effort to empower the creative economy, especially in the webbing business and also the empowerment of IRT to be more productive and able to take advantage of existing free time. This service uses the ABCD (Asset Based Community Development) approach, namely by using mistresses village assets in the form of creative businesses (Woven Crafts) owned by Mrs. Ayu Wulandari then carried out product innovations such as box hantaran. The results of community service with empowerment and economic assistance in order to innovate woven handicraft products both for business and IRT during mentoring and after mentoring provide positive changes.